2019
DOI: 10.1515/cclm-2018-0464
|View full text |Cite
|
Sign up to set email alerts
|

Detection capability of quantitative faecal immunochemical tests for haemoglobin (FIT) and reporting of low faecal haemoglobin concentrations

Abstract: Faecal immunochemical tests for haemoglobin (FIT) are widely used in asymptomatic population screening for colorectal (bowel) cancer. FIT are also used to assist with the assessment of patients presenting with lower abdominal symptoms. Quantitative FIT allow the generation of numerical estimates of faecal haemoglobin (f-Hb) concentrations. There is now great interest in "low" f-Hb concentrations in these clinical settings: in consequence, knowledge of the detection capability is very important for f-Hb concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 24 publications
0
45
0
1
Order By: Relevance
“…FIT detects the globin component of haemoglobin (Hb) by immunoassay and can reliably measure the faecal Hb concentration (f-Hb) to the nearest microgram of Hb per gram of faeces (µg/g). 5 Since 2010, over 25 diagnostic accuracy studies have reported data on the use of FIT in symptomatic patients utilising a range of cut-offs. [6][7][8] In 2014, a study of 787 symptomatic patients from Spain suggested that FIT is more accurate for the detection of CRC than NICE 2005 criteria (CG27) although NICE have since expanded its referral criteria to include lower risk symptoms (NG12).…”
Section: Gi Cancermentioning
confidence: 99%
“…FIT detects the globin component of haemoglobin (Hb) by immunoassay and can reliably measure the faecal Hb concentration (f-Hb) to the nearest microgram of Hb per gram of faeces (µg/g). 5 Since 2010, over 25 diagnostic accuracy studies have reported data on the use of FIT in symptomatic patients utilising a range of cut-offs. [6][7][8] In 2014, a study of 787 symptomatic patients from Spain suggested that FIT is more accurate for the detection of CRC than NICE 2005 criteria (CG27) although NICE have since expanded its referral criteria to include lower risk symptoms (NG12).…”
Section: Gi Cancermentioning
confidence: 99%
“…and a series of proposals made including the following:40  f-Hb concentrations should not be reported to more significant figures than whole integers,  f-Hb concentrations less than the limit of detection (LoD) of the FIT analytical system should be termed "not detected" or "undetectable",  for academic use: f-Hb greater than the LoD could advantageously be documented,  for routine clinical use: numerical f-Hb should be reported only when greater than the limit of quantitation (LoQ): f-Hb less than the LoQ (x) should be reported as < x μg Hb/g faeces and  if a more sophisticated reporting system is required, one option is to report:o f-Hb < LoD = f-Hb not detected o LoD < f-Hb < LoQ = f-Hb detected o f-Hb ≥ LoQ = report the found f-Hb Adherence to these proposals would result in harmonisation of the reporting of f-Hb data, which should facilitate understanding and transferability of information across geography and time.A further controversy is whether the high sensitivity makes FIT a good rule-in test for CRC or the high negative predictive value (NPV) shown in many studies on use of FIT in assessment of the symptomatic10,11 demonstrates that FIT provides a good rule out investigation for SBD. In reality, f-Hb in patients presenting in primary carer with lower abdominal symptoms could be considered as a continuous variable.…”
mentioning
confidence: 99%
“…Current proposals for FIT testing at low concentrations are dependent on accurate LOD and LOQ estimates (7). In this evaluation we have derived these detection characteristics for a commonly used FIT method.…”
Section: Discussionmentioning
confidence: 99%
“…There is on-going debate as to how FIT results should be reported from those that consider the result as "detected"/"not detected" through to quantitative reporting of numeric values (4,7). Given the high imprecision of analysis when sampling is taken into consideration we would caution against quantitative reporting of faecal Hb due to the high uncertainty of measurement.…”
Section: Implications For Research and Practicementioning
confidence: 99%
See 1 more Smart Citation